Cohen syndrome diagnosis using whole genome arrays. Issue 2 (4th October 2010) - Rivera-Brugués, Nuria; Albrecht, Beate; Wieczorek, Dagmar; Schmidt, Heinrich; Keller, Thomas; Göhring, Ina; Ekici, Arif B; Tzschach, Andreas; Garshasbi, Masoud; Franke, Kathlen; Klopp, Norman; Wichmann, H-Erich; et al.
Abstract : Background: Cohen syndrome is a rare autosomal recessive disorder with a complex phenotype including psychomotor retardation, microcephaly, obesity with slender extremities, joint laxity, progressive chorioretinal dystrophy/myopia, intermittent isolated neutropenia, a cheerful disposition, and characteristic facial features. The COH1 gene, which contains 62 exons, is so far the only gene known to be associated with Cohen syndrome. Point mutations, deletions and duplications have been described in this gene. Oligonucleotide arrays have reached a resolution which allows the detection of intragenic deletions and duplications, especially in large genes such as COH1 . Method and results: High density oligonucleotide array data from patients with unexplained mental retardation (n=1523) and normal controls (n=1612) were analysed for copy number variation (CNV) changes. Intragenic heterozygous deletions in the COH1 gene were detected in three patients but no such changes were detected in the controls. Subsequent sequencing of the COH1 gene revealed point mutations in the second allele in all three patients analysed. Conclusion: Genome-wide CNV screening with high density arrays provides a tool to detect intragenic deletions in the COH1 gene. This report presents an example of how microarrays can be used to identify autosomal recessive syndromes and to extend the phenotypic and mutational spectrum of recessive disorders.